ANALISIS DAMPAK PENCEMARAN LINGKUNGAN DENGAN METODE LIFE CYCLE ASSESSMENT (LCA) PADA INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) PT. SURABAYA INDUSTRIAL ESTATE RUNGKUT (SIER) SURABAYA - Hanugrah Sinedyo Yekti; Mohammad Mirwan (EnviroUS, 2021)
In the industrial wastewater treatment process, the treatment of waste that causes environmental pollution. PT Surabaya Industrial Estate Rungkut (SIER) is the oldest industrial estate management company in Indonesia, headquartered in Surabaya, East Java. PT SIER has a wastewater treatment center that processes factory waste and household waste from factories in industrial areas to be neutralized before being channeled into the Tambak Oso River. The industrial wastewater treatment process with the largest contribution in causing an impact on the Distribution Box process unit, North Clarifier, South Clarifier, Oxidation Ditch I, II, III, IV. Therefore, it is necessary to do an alternative strategy to reduce emissions resulting from the processing process. Through the Life Cycle Assessment (LCA) method, environmental impacts can be analyzed, namely any changes that occur in the environment, wholly or partly due to environmental aspects. In this analysis using a gate to gate approach with SimaPro 9.1.0.11. with the IMPACT 2002+ impact analysis method so as to get results that are in accordance with the objectives and conditions that occur in the PT.SIER wastewater treatment plant environment. The data analyzed in this study used the pollutant load data of wastewater per day. The biggest impact category obtained from the results of this analysis is inorganic respiration of 0.334 DALY, global warming of 252000 kg CO2 eq, non-renewable energy of 3730000 MJ. Improvement programs that can be carried out to reduce the environmental impact generated by the methane gas processing wastewater treatment process with anaerobic digestion, making green open land, and updating the installation unit.